Be encouraged: God can turn your trials into triumphs - Wiersbe, Warren W.; (1929-2019) (United Stated of America, 1984)
The road of spiritual growth can get bumpy. From the new believer to the seasoned disciple, we all experience frustrations and setbacks in our pursuit of God. And perhaps no one understands struggles better than the apostle Paul. In the book of 2 Corinthians, Paul shares a revealing look at his own challenges, and offers a profound message of encouragement for every believer. Part of Dr. Warren W. Wiersbe's best-selling BE commentary series, Be Encouraged has now been updated with study questions and a new introduction by Ken Baugh. A respected pastor and Bible teacher, Dr. Wiersbe shares words of hope for your own journey of faith.
Keywords: Religion